2019
DOI: 10.1016/j.ijppaw.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and phylogenetic analysis of Cryptosporidium, Hepatozoon and Spirometra in snakes from central China

Abstract: Snakes are popular as food and traditional medicine in China. However, information about parasitic and bacterial infections in snakes from China is scarce. We investigated the prevalence of selected zoonotic agents including Cryptosporidium, Hepatozoon and Spirometra, in snakes in central China from June to October in 2018 by PCR amplification using parasite-specific primers. PCR amplification and DNA sequencing showed that 10.1% (15/149) of snakes were positive for Cryptosporidium spp., while 2.7% (4/149) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that carnivorous snakes and lizards infected with Cryptosporidium oocysts, possibly from the ingestion of infected rodents, may be asymptomatic [ 70 ]. Furthermore, predator–prey transmission of Cryptosporidium may occur, with Cryptosporidium -infected food maintaining a source of oocysts that are passively transferred through snakes [ 71 ]. As such, Cryptosporidium oocysts can be detected in lizards and snakes even when they are not infected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that carnivorous snakes and lizards infected with Cryptosporidium oocysts, possibly from the ingestion of infected rodents, may be asymptomatic [ 70 ]. Furthermore, predator–prey transmission of Cryptosporidium may occur, with Cryptosporidium -infected food maintaining a source of oocysts that are passively transferred through snakes [ 71 ]. As such, Cryptosporidium oocysts can be detected in lizards and snakes even when they are not infected.…”
Section: Discussionmentioning
confidence: 99%
“…Species identification was performed by nested PCR targeting the SSU rRNA gene with outer primers SSU‐F2 and SSU‐R2 and the inner primers SSU‐F3 and SSU‐R3 after Xiao et al. ( 2019 ). Genotyping relied on the protocol originally described by 2003 targeting the gp60 gene.…”
Section: Methodsmentioning
confidence: 99%
“…DNA samples identified as positive for Cryptosporidium by real-time PCR were subjected to species identification and genotyping. Species identification was performed by nested PCR targeting the SSU rRNA gene with outer primers SSU-F2 and SSU-R2 and the inner primers SSU-F3 and SSU-R3 after Xiao et al (2019). Genotyping relied on the protocol originally described by 2003 targeting the gp60 gene.…”
Section: Subtyping Of Giardia and Cryptosporidiummentioning
confidence: 99%
“…Currently, Cryptosporidium has been identified from domestic mammals ( 7 ), birds ( 8 ), reptiles ( 9 ), amphibians ( 10 ), and fishes ( 11 ). More than 40 species of Cryptosporidium have been identified ( 7 ).…”
Section: Introductionmentioning
confidence: 99%